PERANCANGAN SISTEM HIDROLIK PADA PINTU WINGBOX BERKAPASITAS 2 TON - Jefvin Firnandius; Agus Halim; Agustinus Purna Irawan (POROS, 2022)
Currently, many innovations are being made in developing a technology to facilitate human work. One of these technologies is the hydraulic cylinder. Hydraulic cylinders were created to facilitate human work, especially in the industrial sector. Hydraulic cylinder, using a liquid or so-called liquid fluid, to be able to make the hydraulic cylinder work. In the hydraulic cylinder components, there are cylinder axles, pistons and cover seals. In general, hydraulic cylinders can be used for wingboxes. A wingbox is a box on a truck, which can be opened from the side with the help of a hydraulic cylinder. This journal was created to study how the simulation of hydraulic cylinder components when working. The design method used is the reverse engineering method, where the components that have been designed are then simulation is made to find out how strong the component is in holding the load when the component is working. The simulation is carried out using the Autodesk Fusion 360 application to find out how strong the hydraulic cylinder works in bearing the load. The results of this method are obtained when the simulation results of the hydraulic cylinder have been obtained.